Inclusion of BUMDesa Tax Awareness with Mina Agrowisata in The Self-Assessment System - Asih Machfuzhoh; Intan Puspanita; Refi Pratiwi (MOVE: Journal of Community Service and Engagement, 2021)
The excellent potential that can be developed in villages rich in agricultural or plantation products is village agrotourism. This is one of the most popular tourist destinations. Agrotourism has the potential to be developed into superior tourism and only needs to be developed into a place for tourists to visit. Agrotourism can also involve multiple landowners and communities. Apart from strengthening the independent economy, the government hopes that with economic independence managed by BUmdesa, it will become one of the state's income, through taxes. Many do not understand how the tax treatment of BUM DES BUMDes is an entity in the form of a business entity formed from separated village assets as is the case with BUMN and BUMD. During that time, we know that government programs are not taxed. However, if we understand the explanation of the tax object which can be interpreted as a transaction (usually a source of income) which according to tax regulations is classified as a transaction that must be taxed. Income from a foundation derived from donations and grants is not an object of taxation. BUMDes has operational activities which from these activities can generate profits. Thus, BUMDes has met the requirements as a tax object. Therefore, the tax imposition for BUMDes is corporate tax. Keywords: Village Owned Enterprises, Understanding, Tax Awareness,